Strategies for Understanding Reading Used by Arabic Language Learners at the End of the Preparatory Year - Mutassem Hamad (Şarkiyat Mecmuası)
This study aimed to assess the extent to which learners of the Arabic language possess reading comprehension strategies after completing the preparatory year in Islamic science faculties. It also examined the impact of variables such as gender and place of study on using these strategies. The research was conducted on a randomly selected sample of 120 university students during the academic year 2023-2024. A descriptive-analytical method was employed to achieve the study’s objectives, and a questionnaire with a graded scale comprising 26 strategies was developed. These strategies were categorized into three areas: 1. Pre-reading strategies, 2. During-reading strategies, and 3. post-reading strategies. The findings revealed that preparatory year students frequently used pre-reading and during-reading strategies but only moderately used post-reading strategies. No statistically significant differences were found between male and female students in pre-reading and post-reading strategies, while differences favoring females were observed during-reading strategies. No significant differences were found between pre-reading and post-reading strategies, regardless of the place of study. However, differences in during-reading strategies were noted, with Sabahattin Zaim University ranking first, followed by Kocaeli University. The study recommended that teachers emphasize language learning strategies in their lessons across all skills, guide students toward effective learning strategies, and train them to utilize them, thereby empowering them to enhance their reading comprehension skills.